2013
DOI: 10.7191/jeslib.2013.1024
|View full text |Cite
|
Sign up to set email alerts
|

Common Errors in Ecological Data Sharing

Abstract: Objectives: (1) to identify common errors in data organization and metadata completeness that would preclude a "reader" from being able to interpret and re-use the data for a new purpose; and (2) to develop a set of best practices derived from these common errors that would guide researchers in creating more usable data products that could be readily shared, interpreted, and used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…For example, a review of peer-reviews of data papers (i.e. data and metadata) published in the Ecological Society of America's Data Papers from 2004-2012 indicated that most authors did not provide metadata that was sufficient to support interpretation and re-use of the data (Kervin et al, 2013). Similarly, a recent survey of managers of environmental and ecological data repositories demonstrated that data contributors frequently made errors with respect to how data were organized (83% of the time) and documented (79% of the time) (Kervin et al, 2014).…”
Section: Future Of Data Sharingmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, a review of peer-reviews of data papers (i.e. data and metadata) published in the Ecological Society of America's Data Papers from 2004-2012 indicated that most authors did not provide metadata that was sufficient to support interpretation and re-use of the data (Kervin et al, 2013). Similarly, a recent survey of managers of environmental and ecological data repositories demonstrated that data contributors frequently made errors with respect to how data were organized (83% of the time) and documented (79% of the time) (Kervin et al, 2014).…”
Section: Future Of Data Sharingmentioning
confidence: 98%
“…In 2005, the Ecological Society of America began publishing peer-reviewed Data Papers that consisted of ecological data and detailed metadata that were accompanied by an abstract in the journal Ecology (Kervin et al, 2013). BioMed Central established GigaScience in 2012 to support the publication of biomedical and life sciences data, including ecological data (http://www.…”
Section: The Role Of Publishersmentioning
confidence: 99%
“…Our story is only one potential path because there are many ways to upgrade scientific practiceswhether collaborating only with your 'future self ' or as a team-and they depend on the shared commitment of individuals, institutions and publishers 6,16,17 . We do not review the important, ongoing work regarding data management architecture and archiving 8,18 , work flows 11,[19][20][21] , sharing and publishing data [22][23][24][25] and code [25][26][27] , or how to tackle reproducibility and openness in science [28][29][30][31][32] . Instead, we focus on our experience, because it required changing the way we had always worked, which was extraordinarily intimidating.…”
mentioning
confidence: 99%
“…The outstanding questions are 1) whether this reporting approach will ultimate result in improved availability of data with accompanying high quality metadata, and 2) what the tradeoffs are in terms of person-hours and who bears that cost-the data originator or dedicated data team personnel. We prioritized reporting formats in FRAMES to maximize reporting efficiency because although improving, the generally low quantity of shared data and poor quality of metadata is problematic in the earth sciences (Tenopir et al, 2011;Kervin et al, 2013;Michener, 2015).…”
Section: Lessons Learned and Future Developmentmentioning
confidence: 99%
“…Metadata are essential to describe the different approaches taken to obtain, process, and report diverse ecohydrological and biogeochemical observations and the resulting data products (Michener et al, 1997;Michener, 2006;Papale et al, 2012;Kervin et al, 2013). Metadata allow for interpretation and integration of heterogeneous data obtained from different measurement approaches across disparate study sites, which occur even in well-organized science projects.…”
Section: Introductionmentioning
confidence: 99%